2005
DOI: 10.1089/lap.2005.15.411
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Presentation of Ilio-Iliac Arteriovenous Fistula Following Laparoscopic Cholecystectomy Treated with Percutaneous Graft-Covered Stent Placement

Abstract: Major vascular injuries during laparoscopic cholecystectomy are rare, usually readily apparent, and immediately treated. We report a case of delayed presentation of a retroperitoneal vascular injury. The patient presented with abdominal pain and increasing edema of the lower extremities 1 year after laparoscopic cholecystectomy and was found to have an ilio-iliac arteriovenous fistula. Endovascular treatment was accomplished using a graft-covered polytetrafluoroethylene stent. The patient remained free of symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Gregoric et al [6] first described a case of an aortocaval fistula presenting as acute renal failure. Since then, there have been only three cases [7-9] where the patient has presented with multiorgan failure. This is the second reported case of an endovascular repair of such a patient.…”
Section: Discussionmentioning
confidence: 99%
“…Gregoric et al [6] first described a case of an aortocaval fistula presenting as acute renal failure. Since then, there have been only three cases [7-9] where the patient has presented with multiorgan failure. This is the second reported case of an endovascular repair of such a patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case described, the patient was haemodynamically unstable, requiring inotropic support with renal impairment. It has been suggested that endovascular treatment of arteriovenous fistulas be reserved for elective presentations in stable patients, where there is sufficient time for careful planning of the procedure, and that surgery is more appropriate for patients presenting more acutely, given the lack of experience with endovascular management in this group of patients in the published reports to date 10 . It was felt that endovascular treatment had a high chance of failure in this study, as, unlike a fistula of iatrogenic cause (e.g.…”
Section: Discussionmentioning
confidence: 99%